STRUCTURAL AND PETROLOGICAL EVOLUTION OF THE BORON-IRON TAYOZHNOYE DEPOSIT (CENTRAL ALDAN, RUSSIA) - Pertsev N.N.; Kulakovskii A.L. (My University, 2002)
The contact-metasomatic boron-iron Tayozhnoye deposit located in the central part of the Aldan Shield is unique compared to other skarn deposits with enormous reserves of high-quality ores of iron and accompanying components (especially boron). Furthermore, it occurs just near a coking coal deposit. The process of formation and further geological evolution of the Tayozhnoye deposit is rather complicated and polystage. It includes structural rearrangement and metamorphic and ore-metasomatic alteration of host rocks. The investigation and exploration history of the deposit is prolonged as well. At first (in the 1950), three alternative hypotheses concerning the deposit genesis were discussed: contact-metasomatic, sedimentary-metamorphic, and metasomatic related to the so-called "basification front." The exploration of the deposit in the 1980s, accompanied by extensive underground works and drilling, confirmed the contact-metasomatic hypothesis and allowed one to suggest the polystage genesis of the deposit. The correlations between structure-forming, petrological, and ore-forming processes revealed a close genetic relationship between deformations and magmatic fluid activity under combined cyclic and unidirectional variations of P-T conditions in the Early Proterozoic. Mineralization mega-stages correspond to tectonic deformation episodes marked by changes of the regional stress fields and style of deformations. The most intensive ductile deformations (folding and plastic flow) were restricted to the beginning of the megastages and were not accompanied by any metasomatic events. The inversion of structural deformation type from ductile to dilatant decompaction corresponds to the high-temperature progressive stages, and is characterized by intensive metasomatic rock alteration. Regressive metasomatic processes were commonly associated with brittle deformations. The deep-rooted faults and shear kinematics strongly control the host rock evolution and the formation of the Tayozhnoye deposit, because they favor the penetrable zones' origin. The last are conduits for deep-sourced fluids and tectonic intrusion of ultramafic rocks and marbles. These rocks formed the initial matrix for consequent skarn formation and ore deposition at their contacts with chemically contrasting rocks within the faults. Resulting structures formed some structural and geochemical traps for ore solutions. The first megastage enclosed the plagiogranitization of host rocks, and deposition of small bodies of forsterite-magnetite ores from postmagmatic sodium-hydrochloride solutions. The second megastage is related to the alaskitic granitization and activity of potassic-fluorine postmagmatic fluids. Extensive deposition of magnetite, boron-magnetite ores, sulfide, and boron-silicate mineralization belong to this megastage. No magmatic rocks related to the third megastage are known, but the quartz-feldspar metasomatic rocks formed under rising temperatures do occur. Hydrothermal solutions had a potassic-hydrochloride composition, like those at the second megastage, but they did not deposit any ores. The high-temperature fluids of this megastage were reduced, and low-temperature ones were oxidized.